The Role of Corporate Transparency in Moderating the Influence of Tax Planning and Tax Avoidance on Company Value in Energy Sector Companies Listed on the Indonesia Stock Exchange in 2022-2024 - Ayu Iga Wekasih; Imarotus Suaidah; F Fauziyah (LP2M IAIN Palopo, 2026)
Company value is an important indicator in evaluating business performance and prospects, especially in the energy industry, which is known for its high risks and regulations. The purpose of this study is to investigate the impact of Tax Planning and Tax Avoidance on Company Value with Company Transparency acting as a moderating variable in energy sector companies listed on the Indonesia Stock Exchange for the period 2022-2024. The approach used in this study is quantitative with panel data regression. Based on the Chow, Hausman, and Lagrange Multiplier tests, the most appropriate model is the Random Effect Model (REM). Tax Planning is defined through the Tax Retention Rate (TRR), Tax Avoidance is measured using the Cash Effective Tax Rate (CETR), and Company Value is determined through the Price to Book Value (PBV). The findings of this study indicate that Tax Planning and Tax Avoidance do not have a significant effect on company value. Furthermore, Corporate Transparency is not effective in strengthening this relationship. Overall, these two independent variables also do not contribute significantly to Company Value. The results of this study indicate that tax management strategies are not yet a major factor influencing company value in the energy sector. For future research, it is recommended that the sample be expanded and additional variables be included to obtain more comprehensive results.